Antibiotic-Resistant Bugs in the 21st Century — A Clinical Super-Challenge - Arias, Cesar A; Murray, Barbara E (The New England journal of medicine, 2009)
Drs. Cesar Arias and Barbara Murray write that we have arrived at a point as frightening as the preantibiotic era: for patients infected with multidrug-resistant bacteria, there is no magic bullet. In March 1942, a 33-year-old woman lay dying of streptococcal sepsis in a New Haven, Connecticut, hospital, and despite the best efforts of contemporary medical science, her doctors could not eradicate her bloodstream infection. Then they managed to obtain a small amount of a newly discovered substance called penicillin, which they cautiously injected into her. After repeated doses, her bloodstream was cleared of streptococci, she made a full recovery, and she went on to live to the age of 90. 1 Sixty-six years after her startling recovery, a report 2 described a 70-year-old man in San Francisco with endocarditis caused by vancomycin-resistant . . .